Three Planctomycetes isolated from biotic surfaces in the Mediterranean Sea and the Pacific Ocean constitute the novel species Symmachiella dynata gen. nov., sp. nov. and Symmachiella macrocystis sp. nov. - Salbreiter, Markus (Antonie Van Leeuwenhoek, 2020)
Planctomycetes is a phylum of environmentally important bacteria, which also receive significant attention due to their fascinating cell biology. Access to axenic Planctomycete cultures is crucial to study cell biological features within this phylum in further detail. In this study, we characterise three novel strains, Mal52(T), Pan258 and CA54(T), which were isolated close to the coasts of the islands Mallorca (Spain) and Panarea (Italy), and from Monterey Bay, CA, USA. The three isolates show optimal growth at temperatures between 22 and 24 °C and at pH 7.5, divide by polar budding, lack pigmentation and form strong aggregates in liquid culture. Analysis of five phylogenetic markers suggests that the strains constitute two novel species within a novel genus in the family Planctomycetaceae. The strains Mal52(T) (DSM 101177(T) = VKM B-3432(T)) and Pan258 were assigned to the species Symmachiella dynata gen nov., sp. nov., while strain CA54(T) (DSM 104301(T) = VKM B-3450(T)) forms a separate species of the same genus, for which we propose the name Symmachiella macrocystis sp. nov.